2014
DOI: 10.1111/jon.12173
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Encephalopathy among Ephedron Abusers‐Case Reports

Abstract: Ephedrone encephalopathy is referred to as a group of symptoms of manganese deposition within the central nervous system (CNS), resulting from the abuse of ephedrone (methcathinone), obtained in reaction using the excess amount of manganese-containing oxidants. The diagnosis is based on the contrast-enhanced head MRI findings characteristic for this syndrome, clinical manifestation and history of ephedrone use. The syndrome has been reported in recent years in young people from Eastern Europe and Russia with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
(5 reference statements)
0
7
0
1
Order By: Relevance
“…The most common cause of exposure to excess Mn is occupational, and has been documented in miners (5), welders (6), ferroalloy workers (7), battery manufacturers (8), and glass workers (9). Brain Mn accumulation has also been reported in patients receiving total parenteral nutrition therapy (10,11), patients with hepatic encephalopathy (12), and abusers of ephedrone (methcathinone) (13).…”
mentioning
confidence: 94%
“…The most common cause of exposure to excess Mn is occupational, and has been documented in miners (5), welders (6), ferroalloy workers (7), battery manufacturers (8), and glass workers (9). Brain Mn accumulation has also been reported in patients receiving total parenteral nutrition therapy (10,11), patients with hepatic encephalopathy (12), and abusers of ephedrone (methcathinone) (13).…”
mentioning
confidence: 94%
“…Over the last decade, numerous clinical reports from eastern and western European countries, Russia, and Canada have shown that young individuals who abuse ephedron (also called methcathinone) rapidly present (approximately 6 months after use) with emotional, cognitive, and movement abnormalities similar to those in Mn-induced parkinsonism, which continue to persist even after drug abstinence (Colosimo and Guidi, 2009;de Bie et al, 2007;Fudalej et al, 2013;Iqbal et al, 2012;Janocha-Litwin et al, 2014;Meral et al, 2007;Poniatowska et al, 2014;Sanotsky et al, 2007;Selikhova et al, 2008;Sikk et al, 2010Sikk et al, , 2013Stepens et al, 2008;Yildirim et al, 2009). These recreational ephedron users are reminiscent of parkinsonian cases discovered in the early 1980s, where irreversible parkinsonism was induced by the intravenous injection of an illicit opiate analog (meperidine) that was incorrectly synthesized into the nigrostriatal dopaminergic neurotoxicant 1-methyl-4-phenyl-1,2,3,6tetrahydropyridine (MPTP) (Davis et al, 1979;Langston et al, 1983).…”
Section: Parkinsonism In Intravenous Ephedron Usersmentioning
confidence: 99%
“…However, unlike methamphetamine synthesis, potassium permanganate is used for the homemade production of ephedron, thereby creating high levels of Mn byproduct (Sikk et al, 2007). Ephedron users consequentially have increased blood Mn levels due to their intravenous injection of this homemade mixture (Fudalej et al, 2013;Janocha-Litwin et al, 2014;Poniatowska et al, 2014;Selikhova et al, 2008;Sikk et al, 2010Sikk et al, , 2013Stepens et al, 2008). As observed with occupational exposures to Mn toxicity, these individuals are levodopa-resistant (Colosimo and Guidi, 2009;Fudalej et al, 2013;Janocha-Litwin et al, 2014;Poniatowska et al, 2014;Sanotsky et al, 2007;Selikhova et al, 2008;Sikk et al, 2013;Stepens et al, 2008) and displayed abnormally high Mn concentrations in T1-weighted MRI images of the globus pallidus, striatum, and midbrain (Fudalej et al, 2013;Janocha-Litwin et al, 2014;Poniatowska et al, 2014;Selikhova et al, 2008;Sikk et al, 2010Sikk et al, , 2013Stepens et al, 2008).…”
Section: Parkinsonism In Intravenous Ephedron Usersmentioning
confidence: 99%
See 1 more Smart Citation
“…When the homeostatic mechanisms of the gut, which regulates gastrointestinal Mn absorption, and/or the liver, which modulates the biliary excretion of Mn, fail, get bypassed or are overwhelmed, rising Mn blood levels subsequently result in Mn deposition in the brain 6 7 . Mn overexposure can occur in welding and mining industries, in individuals using Mn contaminated Ephedrone preparations, and in patients receiving high Mn concentrations in total parenteral nutrition 8 9 10 . Impaired hepatic Mn excretion in chronic liver disease may cause ‘acquired hepatocerebral degeneration' 11 .…”
mentioning
confidence: 99%